Educação em ciências nos anos iniciais: interface entre saberes num contexto de especificidade docente - Pereira Sobrinho, Osleane Patrícia Gonçalves (Universidade Federal de São Carlos, 2022)
Brazilian education has its historical context marked by changes and reforms that led to advances and setbacks, a movement that is still continuous in current times and in which the teaching of science is included, which in the educational context of Brazil is guided by the search for the rise in meaningful ways of learning scientific knowledge. Looking for reflections beyond the pointing of obstacles to be overcome for the effective improvement of the quality of science teaching in the early years of elementary school, the analyses carried out here intend to approach the relationship between knowledge, actions and pedagogical practices of a group of teachers from the city of Campo Grande/MS who are in the condition of specificity of science teaching in this pedagogical stage, considering aspects of the teaching activity in the way these professionals express it in the mobilization of knowledge in the teaching of scientific knowledge, in view of possible contributions on the teaching of science in the early years of elementary school. The investigative design occurs within the framework of a Case Study (YIN, 2001), with the use of a questionnaire and focus group dynamics for data collection, which in turn were analyzed with the help of Content and Enunciation analysis (BARDIN, 2011). The discussions of the analysis focus on elements of teaching as professional development and pedagogical knowledge mobilized in the context of educational practice in science in the early years, based on the studies of Tardif (2012) and Tardif and Lessard (2014). The results point to the following conclusions: the teachers participating in the research are in a situation of semi-professionalism, due to the weaknesses in terms of professional development raised in several areas and that have repercussions on the understanding that the teaching activity of science in the early years should not require the teacher to be a specialist as "expected" from graduates in the area of Natural Sciences; nor should it lead them to assume a condition of specialist within the pedagogical training recommended for this phase of education (Pedagogy). Thus, the understanding presented is that science teaching in the early years of elementary school is constituted by the interface between teachers' knowledge and classroom realities, knowledge mediated by dimensions of practice in which the conditioning elements can be configured both as drivers and as "real" obstacles to be faced. In this sense, one of the paths for the effective insertion of science teaching in the early years involves the empowerment of teachers, since teachers are the transforming agents of the curriculum to be taught and it is in this action that the relevance of science teaching should be imbricated.
Science Education in the elementary school: knowledge interface in the context of teacher specificity
Keywords: Ensino de ciências; Anos Iniciais do Ensino Fundamental; Desenvolvimento profissional docente; Saberes docentes; Prática pedagógica; CIENCIAS HUMANAS::EDUCACAO::ENSINO-APRENDIZAGEM